ANALYSIS OF SUPPORTING AND INHIBITING FACTORS FOR THE IMPLEMENTATION OF EDUCATION MANAGEMENT INFORMATION SYSTEM POLICIES AT MADRASAH IBTIDAIYAH AL-ADLI PALEMBANG - Mira Marisa Mira; Effendi Nawawi; Arif Rahman Hakim; Femi Asteriniah; Nopriawan Mahriadi (SOSIOEDUKASI, 2026)
This study aims to analyze the supporting and inhibiting factors for the implementation of the Education Management Information System (EMIS) policy at Madrasah Ibtidaiyah Al-Adli Palembang. This study used a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The analysis was conducted using SWOT analysis theory. The results showed that the resource aspect is a key supporter and obstacle to EMIS implementation. The main obstacles were found in the resource dimension, which included limited dedicated budget, lack of adequate hardware, internet network disruptions, and the dual workload of operators who also serve as teachers.